Hydrodynamic Mixed Convection in a Lid- Driven Porous Square Cavity with Internal Heat Generating Elliptic Block - Bhuiyan, Abdul Halim; Munshi, M Jahirul Haque (GANIT: Journal of Bangladesh Mathematical Society, 2018)
Hydrodynamic mixed convection in a lid-driven porous square cavity with internal heat generating elliptic block is numerically simulated in this paper by employing finite element method. The working fluid is assigned as air with a Prandtl number of 0.71 throughout the simulation. The top lid moves left to right at a constant speed (U0)with cold temperature and while the bottom lid moves right to left at a constant speed (−U0) with hot temperature. The left wall is heated while the right wall is linearly heated and heat generating elliptic block is placed at the center of square cavity. The effects of governing parameters in the present study are namely, Rayleigh number Ra, Darcy number Da, Grash of number Gr. The effects of heat generation and the porosity of the medium on the streamlines, isotherms, temperature profiles, velocity field and average Nusselt numbers are presented in graphical and tabular forms and discussed. An optimum combination of the governing parameters would result in higher heat transfer. Moreover, it is observed that both the Darcy number and moving lid ordination have significant effects on the flow and thermal fields in the enclosure. GANIT J. Bangladesh Math. Soc.Vol. 37 (2017) 175-183